Changes in body composition and substrate utilization after a short-term ketogenic diet in endurance-trained males - McSwiney, Fionn T.; Fusco, Ben; McCabe, Lochlann; Lombard, Andrew; Crowley, Patrick; Walsh, Jack; Hone, Michelle; Egan, Brendan (Biology of Sport, 2021)
Few studies have investigated the short-term effects of a very low carbohydrate ketogenic diet (KD) on body composition and substrate utilization in trained individuals. This study investigated effects on substrate utilization during incremental exercise, and changes in body composition, in response to seven days ad libitum consumption of a KD by athletes from endurance sports. Nine young trained males (age, 21.8 ± 1.9 y; height, 1.83 ± 0.11 m; body mass, 78.4 ± 13.8 kg; body fat, 14.9 ± 3.9%; VO2peak, 54.3 ± 5.9 mL kg-1 min-1) were assessed before (day 0; PRE) and after (day 7; POST) seven days of consuming an ad libitum KD. Following an overnight fast, body composition was measured by dual x-ray absorptiometry, and substrate utilization was measured during an incremental (3 min stages, 35 W increments) exercise test on a cycle ergometer. After KD, Wmax (PRE, 295 ± 30 W; POST, 292 ± 38 W) and VO2peak (PRE, 4.18 ± 0.33 L min-1; POST, 4.10 ± 0.43 L min-1) were unchanged, whereas body mass [-2.4 (-3.2, -1.6) kg; P < 0.001, d = 0.21], fat mass [-0.78 (-1.10, -0.46) kg; P < 0.001, d = 0.22] and fat-free mass (FFM) [-1.82 (-3.12, -0.51) kg; P = 0.013, d = 0.22] all decreased. The respiratory exchange ratio was lower, and rates of fat oxidation were higher, at POST across a range of exercise intensities. Maximal fat oxidation rate was ~1.8-fold higher after KD (PRE, 0.54 ± 0.13 g min-1; POST, 0.95 ± 0.24 g min-1; P < 0.001, d = 2.2). Short-term KD results in loss of both fat mass and FFM, increased rates of fat oxidation and a concomitant reduction in CHO utilization even at moderate-to-high intensities of exercise.